Privacy and Customization of Clusters with Application Development - Pallavi; Chandana; Rekha Sahithi; Shwetha; Devi, Sumithra (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This paper presents a high level view of how clusters are being used in large number of domains for preserving and protecting the data. Because of these , clusters are being exposed to many attacks coming from open network.. Hence there are many methods to design a privacy preserving clusters. To ensure these preserving clusters, cluster validity measurements are done for different type of Data. Protocols are used to do the privacy preserving. The clusters analysis are used in banking sector for identification of the bank customer profile. Algorithms are used to find the Sensitive data before making the individual data into clusters of data .and then the privacy is applied only on these sensitive data.